2011
DOI: 10.1352/1944-7558-116.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Social Determinants of Caregiver Burden Among Families of Children With Developmental Disabilities

Abstract: This study described predictors of caregiver burden among parents of children with developmental disabilities. The sample, obtained from the 2005-2006 National Survey of Children With Special Health Care Needs, included 12,225 children, aged 5 to 17 years, with a developmental disability. Structural equation modeling assessed the relationships between the factors of Caregiver Burden, Ease of Accessing and Navigating the Health Care System, and Unmet Health Care Needs. Caregiver burden was inversely associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 48 publications
(84 reference statements)
4
30
0
1
Order By: Relevance
“…Families that lacked enabling factors for healthcare utilization had higher odds of family time burden, suggesting that access to health services is an important mechanism for reducing the time family members must spend on tasks related to their child's healthcare. Consistent with previous research (Kuo et al, 2011a;McManus et al, 2011;Miller et al, 2015;Turchi et al, 2009), we found that, even after accounting for child's health, families with public health insurance (alone or in combination with private insurance), and those without a medical home, had high odds of time burden for both arranging/coordinating and providing health care for the child at home. Past research shows that key components of the medical home for reducing time burden include family-centered care, care coordination, and obtaining needed referrals (Miller et al, 2015).…”
Section: Implications Of Research Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…Families that lacked enabling factors for healthcare utilization had higher odds of family time burden, suggesting that access to health services is an important mechanism for reducing the time family members must spend on tasks related to their child's healthcare. Consistent with previous research (Kuo et al, 2011a;McManus et al, 2011;Miller et al, 2015;Turchi et al, 2009), we found that, even after accounting for child's health, families with public health insurance (alone or in combination with private insurance), and those without a medical home, had high odds of time burden for both arranging/coordinating and providing health care for the child at home. Past research shows that key components of the medical home for reducing time burden include family-centered care, care coordination, and obtaining needed referrals (Miller et al, 2015).…”
Section: Implications Of Research Findingssupporting
confidence: 89%
“…Need factors, including the severity and instability of the child's condition, and specific diagnoses, are important predictors of time spent providing health care for the child at home and arranging/coordinating care. These findings concur with those of previous studies that identified families of children who were severely and frequently affected by their conditions, or whose health care needs frequently changed, as experiencing the highest time burdens (Bramlett et al, 2009;DuPaul et al, 2013;Kuo et al, 2011b;McCann et al, 2012;McManus et al, 2011;Okumura et al, 2009;Schuster et al, 2011). Measures of stability and severity, based on health status questions like those on the NS-CSHCN (NCHS, 2011), could provide relatively simple ways for clinicians to screen patients for high risk of time burden.…”
Section: Implications Of Research Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Previous research suggests caregivers of children with disabilities experienced greater caregiver stress and related this to coordinating and managing multiple appointments. 20 Thus, it is plausible that the psychosocial burden of caring for a child with a disability negatively influences parents' capacity to engage with therapy services as frequently as parents of children with developmental delays. Moreover, it is also possible that the therapy treatment regimens for children with DX are more complex and involved, which precludes many families, particularly those with limited resources, from engaging fully, which has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver burden is defined as “the time and financial demands associated with caring for a child with disability that constrain the parental social role” (10). Most CSHCN are cared for by a parent who takes on the role of informal caregiver (11).…”
Section: Introductionmentioning
confidence: 99%